Sustainable Utilization of Natural Resources - Mondal, Prasenjit; Dalai, Ajay K (CRC Press, 2017)
Increased research is going on to explore the new cleaner options for the utilization of natural resources. This book aims to provide the scientific knowhow and orientation in the area of the emerging technologies for utilization of natural resources for sustainable development to the readers. The book includes production of energy and lifesaving drugs using natural resources as well as reduction of wastage of resources like water and energy for sustainable development in both technological as well as modeling aspects.